Efektivitas Penggunaan Media Games Edukasi Berbasis Teknologi: Wordwall Terhadap Motivasi Belajar Siswa - Renata, Zabina; Oktavia, Irna; Irawan, Dedi; Rohmaturobbi, A Naji; Pebrianto, Anggi; Nurhidayati, Laela; Anggia, Indry Puspita (Pendidikan Matematika FKIP Universitas Mataram, 2024)
In the digital era, technology has permeated various aspects of life, including education. One popular implementation is the use of educational games such as Wordwall, which has been proven to enhance students' learning motivation. This study aims to evaluate the effectiveness of Wordwall on students' learning motivation in Indonesia. The research employs content analysis methods on relevant literature collected from various academic sources. The results show that Wordwall increases students' intrinsic motivation from 60% to 85%, extrinsic motivation from 55% to 80%, and interest in lessons from 65% to 90%. This improvement aligns with Social Cognitive Theory and ARCS theory, emphasizing the importance of interactive media and material relevance in boosting learning motivation. These findings are consistent with previous research indicating that technology-based learning media effectively enhances students' learning motivation. Therefore, integrating Wordwall into the curriculum can create a more interactive and effective learning environment and improve the quality of education in Indonesia.